Bruxismo do sono e em vigília em adolescentes: prevalência, fatores associados e análise de caminhos - Sara Oliveira Aguiar (2022)
Bruxism is a behavior, with masticatory muscle activity, which can present itself as sleep bruxism (SB) and awake bruxism (AB). It has a multifactorial etiology, and is little explored among adolescents. This thesis is composed of two articles assessing prevalence, associated factors, and path analysis. The objective of article 1 (n=403) was to recognize the pathways influencing the occurrence of probable sleep bruxism (PSB) and probable awake bruxism (PAB) in adolescents. Paper 2 (n=342) aimed to evaluate the association between PSB and biting habits, life satisfaction, sleep characteristics and chronotype profile in adolescents by means of a case-control study. After approval by the institutional ethics committee, adolescents aged 12 to 19 years, regularly enrolled in public and private schools in Belo Horizonte, Brazil, participated in the study. Parents/caregivers answered a questionnaire about their children's sleep characteristics. The adolescents answered the following instruments: a questionnaire about biting habits, sleep characteristics and bruxism report; the Circadian Energy Scale (CIRENS), to measure the chronotype profile; and the self domain of the Brazilian version of the Multidimensional Life Satisfaction Scale for Adolescents (MLSSA). The PSB and PAB were measured considering the positive self-report, added to the presence of attrition dental wear measured in a clinical examination performed by a previously calibrated researcher. Descriptive analysis was included in articles 1 and 2. Article 1 used path analysis, a technique that describes the directed dependencies among a set of variables. In article 2, conditional logistic regression (OR) was performed (p<0.05). As results in article 1, it was found that 22.3% of the adolescents presented PSB and 51.1% PAB. The two manifestations of bruxism showed an association with each other, with a moderate and positive correlation (β= 0.390). Sleep quality and family income had a direct effect on PSB (β= - 0.138; β=0.123; respectively) and on PAB (β= -0.155; β=0.116; respectively), so that those with higher income and poor sleep quality tended to show likely bruxism in both SB and AB. Chronotype had a direct effect on PSB, such that adolescents with morning chronotype tended to have the behavior (β= -0.102). Adolescents who reported drooling on the pillow while sleeping (β= 0.184) and/or who had restless sleep (β= 0.104) tended to present PSB. In artgid 2, on the other hand, it was found that poor sleep quality (OR=1.731, 95%CI 1.054-2.842, p=0.030), habit of biting objects often (OR=3.303, 95%CI 1.631-6.690, p=0.001), habit of biting or tightening lips sometimes (OR=2, 134, 95%CI 1.230-3.702, p=0.007) and biting or lip-squeezing often in the two weeks prior to evaluation (OR=2.355, 95%CI 1.203-4.608, p=0.012) were associated with the occurrence of PAB. It was concluded with article 1 that the chronotype profile, family income and sleep characteristics influence the path taken by PSB, while income and quality of sleep influence PAB. In article 2, it was concluded that adolescents with poor sleep quality and those with biting habits were more likely to present PAB.